Perceptions of quality for graduate athletic training education - Seegmiller, J. G. (Journal of Athletic Training, 2006)
Context: Accreditation is generally considered the primary mechanism for quality assurance in higher education, but disagreement often exists between accrediting agencies and the perceptions of professionals who feel the accrediting body has failed to meet its quality control function. For accreditation to have value, it must be a meaningful indicator of quality and be viewed as such.